L'accès inégalitaire des femmes à la propriété foncière en république du Bénin : mise en perspective du décalage entre droit étatique et droit coutumier - Djima Radji, Asmaou A. A. A. (Université du Québec à Montréal, 2022)
L’accès des femmes aux ressources foncières en Afrique, et plus particulièrement au Bénin, demeure une question fondamentale. Pourtant, maillon clé du développement économique et social béninois, les droits fonciers des femmes se trouvent limités par l’application de règles coutumières, que renforce une certaine ineffectivité du droit étatique. Ce mémoire a pour objectif de faire une mise au point sur cette concurrence des normes en matière d’accès à la propriété foncière des femmes. En effet, en milieu rural, la vie tant sociale que juridique est majoritairement gouvernée par des pratiques coutumières. Alors que les femmes participent activement à la vitalité économique du pays, notamment en cultivant la terre, elles restent discriminées dans l’accès à la propriété des ressources foncières. Cet état des lieux constitue le point d’ancrage de ce mémoire. Il s’agira de comprendre l’effet de cette dualité juridique et de proposer quelques suggestions susceptibles de favoriser l’accès des femmes béninoises à la propriété foncière. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : femme.s, propriété foncière, accès, terre, droit coutumier, droit étatique, droits fonciers, Bénin, Afrique, Afrique de l’Ouest
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; afrique; biblioFem*; bénin; discipline; discriminations; droit; droits des femmes*; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; thématiques

Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Rapport sur le développement humain en Afrique 2016 : accélérer les progrès en faveur de l'égalité des genres et de l'autonomisation des femmes en Afrique (PNUD, 2016)
Les disparités entre les genres coûtent quelque 95 milliards de dollars US par an en moyenne à l’Afrique subsaharienne et ont culminé à 105 milliards de dollars de pertes en 2014 (soit 6 % du PIB régional), compromettant de ce fait les efforts du continent en faveur d’un développement humain et d’une croissance économique inclusifs, indique le Rapport. Le rapport du PNUD analyse les facteurs politiques, économiques et sociaux qui entravent la promotion de la femme en Afrique et propose des politiques et des mesures concrètes pour combler l’écart entre les genres. Il s’agit notamment de corriger la contradiction entre la législation et la pratique afin de passer d’une égalité des genres juridique à une égalité de fait, de rompre avec les normes sociales préjudiciables aux femmes et de transformer les cadres institutionnels discriminatoires, en vue de garantir la participation économique, sociale et politique des femmes. D’après le rapport, une augmentation de 1 % de l’indice d’inégalité de genre contribuerait à réduire l’indice de développement humain (IDH) d’un pays de 0,75 % [...]
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; afrique; approches et analyses; autonomisation; discipline; inégalités; pauvreté; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; égalité des sexes; épistémologie

Travail-famille : un défi pour les femmes à Cotonou - Adjamagbo, Agnès; Gastineau, Bénédicte; Kpadonou, Norbert (Recherches Feministes, 2016)
En Afrique de l’Ouest, le taux d’activité des femmes est élevé. Souvent cantonnées dans le secteur informel, elles contribuent pourtant de façon  importante aux revenus du ménage. Toutefois, les rôles socialement prescrits imposent aux femmes la quasi-intégralité des tâches domestiques et des soins aux enfants. Cet article étudie la manière dont  les femmes actives à Cotonou, au Bénin, gèrent leur quotidien entre contraintes familiales et obligations professionnelles. L’analyse montre  que la conciliation incombe à toutes les femmes, quel que soit leur milieu socioéconomique. La différence se joue plutôt dans les ressources sociales et financières dont elles disposent pour pallier le fardeau de  la double journée.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; approches et analyses; bénin; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; double journée de travail; démographie; famille; inégalités; maternité; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Leading in disadvantaged Zimbabwean school contexts: Female school heads’ experiences of emotional labour - Zikhali, Joyce; Perumal, Juliet (Educational Management Administration and Leadership, 2016)
This qualitative multiple case study explored the sources of emotional stress experienced by 12 female Zimbabwean primary heads leading in socio-economic disadvantaged schools in Masvingo District and their attempts to alleviate the challenges that the children from these disadvantaged contexts presented them with. Data was generated through individual semi-structured interviews, and observations and the data was analysed thematically to elicit the sources of their emotional labour that emanated from stress-related cultural and contextual factors. The study revealed that despite the school heads experiencing anxiety, pain, sorrow, sympathy, frustration, sadness, and concern they were happy about their appointments to leadership positions. The sources of their emotional stress were related to the plight of children; stereotypical gender expectations; lack of parental cooperation; and unrealistic professional and social expectations. The study suggests wellness recesses; the establishment of social networks through which heads could share their experiences; and professional development programmes on stress management as possible interventions that could help the heads deal with these stressful circumstances. © 2015, © The Author(s) 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; directrices d'école; enfants orphelins; environnement; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail émotionnel; zimbabwe; éducation

Chroniques d'une musulmane indignée - Ibnouzahir, Asmaa (Fides, 2015)
En plus d'un récit autobiographique racontant les défis qu'elle a relevés en tant que jeune immigrante musulmane d'origine marocaine arrivée au Québec en 1994, Asmaa Ibnouzahir présente également une analyse éclairante sur des questions qui reviennent souvent dans nos médias au sujet de l'islam, des femmes et de la société: les musulmans «modérés», les crimes «d'honneur», le foulard, le féminisme islamique et bien d'autres. Islamiste pour certains et hérétique pour d'autres, Asmaa Ibnouzahir partage avec nous son parcours personnel et militant qui a fait d'elle la citoyenne québécoise musulmane, féministe et indignée qu'elle est aujourd'hui. Engagée dans les débats sociopolitiques qui ont traversé le Québec au cours de la dernière décennie, sur la religion, l'immigration et les valeurs québécoises, Asmaa Ibnouzahir livre un témoignage essentiel qui donne un accès sans précédent aux coulisses de ces débats. Depuis une dizaine d'années, Asmaa Ibnouzahir est engagée dans la réflexion et les débats sociaux autour des droits de la personne, notamment sur les questions touchant autant à l'immigration et à la religion dans la sphère publique qu'au statut des femmes dans l'Islam. Elle a également voyagé et travaillé dans plus d'une quinzaine de pays en tant que spécialiste de la nutrition d'urgence humanitaire. -- [Renaud-Bray].
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; amériques; approches et analyses; canada; com5170; corps; cours; discipline; droits des femmes*; droits des personnes; féminisme islamique; immigration; maroc; point de vue situé; premier cycle; périodes historiques; québec; religion; régions géographiques; science politique; science politique et droit; thématiques

Gender and the political economy of land in Africa - Kouamé, Euphrasie B.H.; Fofona, Namizata B. (UNU-INRA Working Papers, 2015)
Evidence shows that secure land rights have positive effects on poor people in general and women in particular, especially where households previously had little security. Several countries in Africa have been undertaking land reform initiatives that prohibit gender-based discrimination; however, the results revealed a substantial gap between the development of laws and their effective implementation. This paper draws attention to the political systems within which land tenure and property rights operate, especially for women. It also points out the main challenges in securing women’s land rights in Africa and highlights the economic, social and environmental benefits of increasing women’s access to land. The analysis shows that although many of the changes in policy and law appear to be legal and technical, access to and control over land is in practice related to socio-economic characteristics and governed by cultural practices and power relations at the family, community and country levels. The paper therefore recognizes the need for innovative approaches that go beyond property rights in operationalising strategies that strengthen women’s access to land. It is not enough for land legislation to be gender-sensitive; it must be gender-transformational. Land markets could potentially contribute to this transformation but their role is still limited by poor institutional capacity. The roles that different actors (women, men, women’s organizations, community leaders, donors) can play would be crucial in the process of securing women’s access to land in Africa.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; femmes*; genre; identités LGBTQIA2+; politique; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; égalité des sexes

Plaisirs croisés: gukuna-kunyaza. Missions, corps et sexualités dans le Rwanda contemporain - Michela Fusaschi (Genre, Sexualité et Société, 2012)
Based on ethnographic research in post-genocide Rwanda, this article analyzes how femininity is embodied through a ritual practice called gukuna, which consists of the elongation of the labia minora through a reciprocal massage between young women. This social construction of the female body, in addition to kunyaza, a traditional male sexual technique, is expected to facilitate pleasure during sexual intercourse. Through an analysis of colonial period texts as well as recent interviews, this article shows how this ritual, has persisted in the country despite its condemnation by the Catholic Church since the colonial time, and explores how it is being reinterpreted by women.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afro-féminisme; approches et analyses; corps; cours; discipline; féminisme africain; gukuna; premier cycle; périodes historiques; rituel; rwanda; régions géographiques; science politique; science politique et droit; sex2283; sexualité; thématiques

Identifications homosexuelles, construction identitaire et tensions postcoloniales entre le Cameroun et la France - Awondo, Patrick (L’Espace Politique, 2011)
L’article problématise la circulation de l’« identité homosexuelle » dans l’entre-deux de l’Occident et de l’Afrique. À partir de l’exemple camerounais, il montre comment des « tensions postcoloniales » parasitent le débat autour de l’homosexualité en se cristallisant notamment sur l’affrontement symbolique entre ordres moraux opposés. Au-delà des identifications sexuelles, l’analyse aborde aussi la situation des individus qui tentent par la migration d’échapper au régime de contrainte camerounais et se retrouvent dans la posture de « réfugié (homo)sexuel » en France, sans que pour autant la question de leur « identité » sexuelle soit « résolue ».
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; afrique; approches et analyses; cameroun; cours; discipline; europe; france; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Les monologues voilés - Roosen, Adelheid; Germain, Greg; Drissi, Jamila (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte

Égalité femmes-hommes en Afrique de l'Ouest (Secrétariat du Club du Sahel et de l'Afrique de l'Ouest)
En Afrique de l’Ouest, de grandes inégalités entre les sexes persistent. Les femmes et les filles sont défavorisées dans de nombreux domaines et n’ont pas les mêmes opportunités que leurs homologues masculins. Le Secrétariat du CSAO a compilé les documents relatifs aux politiques et stratégies en matière de genre pour faciliter l’accès aux politiques et cadres institutionnels existants et leur diffusion.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; inégalités; politique; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; égalité des sexes; égalité femme*-homme